André Malraux, théoricien de l’art - Laurent, Thierry (Literatūra, 2017)
André Malraux is a major writer of the twentieth century. We know him as an engaged intellectual and a novelist. His books on art are less read than the rest of his work. Academics and historians have never taken them seriously. Even if they are not of great scientific rigor, they show an original thought expressed in a flamboyant style. Malraux does not write a new story of art but he proposes a philosophical reflection on its riddle. Using many examples of paintings and sculptures produced by various civilizations, Malraux seeks their similarities and imagine their improbable dialogue. He insists on some ideas: art unites people through History and allows both to defy reality and destiny. He values the concept of metamorphosis of our view of the masterpieces of the past.